2018
DOI: 10.1037/men0000096
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style and risk of muscle dysmorphia in a sample of male bodybuilders.

Abstract: In Western countries, body image has become an essential feature of male representations in recent decades. This is especially true of prominent muscularity, which has been traditionally linked with the concept of masculinity. This tendency has also emerged in the Italian context where it was easily assimilated into the traditional Italian stereotype of men being strong and virile. In this context, the practice of bodybuilding has progressively gained popularity as a means of achieving an ideal body image. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 72 publications
4
29
0
Order By: Relevance
“…However, it is unclear if MD leads to difficulties with body contact and sexuality, or if the attempt to attain a powerful body is an attempt to compensate for feelings of inadequacy, vulnerability and a negative self-concept. The latter would be supported by a study of Fabris et al [ 38 ], who found an association between a risk for MD and more insecure (especially avoidant) attachment styles. Insecure attachment styles are characterized by more negative models of self and others, caused by early developmental experiences [ 39 ].…”
Section: Discussionmentioning
confidence: 68%
“…However, it is unclear if MD leads to difficulties with body contact and sexuality, or if the attempt to attain a powerful body is an attempt to compensate for feelings of inadequacy, vulnerability and a negative self-concept. The latter would be supported by a study of Fabris et al [ 38 ], who found an association between a risk for MD and more insecure (especially avoidant) attachment styles. Insecure attachment styles are characterized by more negative models of self and others, caused by early developmental experiences [ 39 ].…”
Section: Discussionmentioning
confidence: 68%
“…Even in the Italian context, the body standard for men is more muscular than the average male body shape (Zelli et al, 2010; Gilli and Ruspini, 2014). The traditional Italian stereotype of men is one of strength and virility; in this context, muscularity has been traditionally linked to the concept of masculinity (Fabris et al, 2017). Nevertheless, nowadays alongside the traditional image of the virile and powerful man, a new type of masculinity has emerged (Boni, 2004, 2007), the so-called ‘metrosexual’ man, who is particularly concerned with the care of the body, is a strong consumer of cosmetics, and is interested in aesthetics (Capellani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other medical or psychological studies contribute to the discourse of 'insecure masculinity', sometimes in unexpected ways. For example, Fabris et al (2018) argue that bodyimage concerns are a central motive for PIED use, although their own findings undermine such a conclusion. They open their article on 170 male body builders in Italy, 14% of whom used steroids, by claiming that 'Italian male representations are in crisis because women have acquired more power in their families and places of work' (Fabris et al, 2018: 273).…”
Section: Discourses Of Disordered Masculinity In Post-2005 Literaturementioning
confidence: 93%